2020
DOI: 10.3329/bjsir.v55i3.49394
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid analysis, cytotoxicity, antimicrobial and antioxidant activities of different extracts of the flowers of Nyctanthes arbor-tristis L.

Abstract: The fatty acid analysis and biological activity of n-hexane, dichloromethane, ethyl acetate and methanol extracts of Nyctanthes arbor-tristis L. flowers are reported. Five fatty acids namely palmitic (44.15%), stearic (19.34%), arachidic (15.06%), behenic (9.77%) and lignoceric (11.69%) acids were identified. From cytotoxicity test, the LC50 values (the median lethal concentration) for n-hexane, dichloromethane, ethyl acetate and methanol extracts as well as for standard vincristine sulphate were found 7.05, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In MIC assay, as shown in g. 3a, CSB inhibited the growth of E.coli strains when compared to the standard drug Ampicillin. This study is in agreement with ndings that showed the antibacterial activity of the owers of NAT [35][36][37]. The lowest concentration at which visible growth of Gram negative human bacteria E.coli strains 1 and 2, ATCC E.coli and K.pneumonia were inhibited at 24 hours of culture was seen at 1.5625µg/ml, 12.5µg/ml, 25µg/ml and 6.25µg/ml which gave percentage inhibition of 47.5%, 65.3%,57.1% and 55.6% respectively.…”
Section: Antibacterial Screeningsupporting
confidence: 93%
See 3 more Smart Citations
“…In MIC assay, as shown in g. 3a, CSB inhibited the growth of E.coli strains when compared to the standard drug Ampicillin. This study is in agreement with ndings that showed the antibacterial activity of the owers of NAT [35][36][37]. The lowest concentration at which visible growth of Gram negative human bacteria E.coli strains 1 and 2, ATCC E.coli and K.pneumonia were inhibited at 24 hours of culture was seen at 1.5625µg/ml, 12.5µg/ml, 25µg/ml and 6.25µg/ml which gave percentage inhibition of 47.5%, 65.3%,57.1% and 55.6% respectively.…”
Section: Antibacterial Screeningsupporting
confidence: 93%
“…Natural plants are known to possess polyphenolic compounds responsible for antioxidant activity and previous phytochemical screening showed the presence of these polyphenolic compounds in the owers of NAT [37]. Different ower extracts of NAT has also showed antioxidant activity [37,43]. These bioactive compounds in and endophytes can donate hydrogen to free radicals thereby disrupt the free radical chain reaction by acting as CSB-capping [44], making the synthesized CSB served as hydrogen donors and reducing agents as seen in this study.…”
Section: Reducing Powermentioning
confidence: 68%
See 2 more Smart Citations